The role of MIS in the negotiation process "An Analytical Study in a Sample of Iraqi Organizations" - داوي, جاسم مشتت; بولص, نداء حازم (Journal of Economics and Administrative Sciences, 2009)
Negotiation is considered as one of the most important kinds of communication in the contemporary organizations, which depend on the important role of managerial information systems in providing necessary and suitable information for success of the negotiation process.Accordingly, this study aims at measuring the extent of the variables effect of managerial information system in the negotiation process.To achieve this study, two hypotheses were chosen; the first is the correlation relation and the second is the effect, and statistical means represented by correlation coefficient "Spearman" and (R2) were used. A Number of conclusions were reached among which the important role that managerial information systems play in the negotiation activity and recommendations are also given.